Aging is associated with prolonged hospitalisation stay in pyogenic liver abscess - A 1:1 propensity score matched study in elderly versus non-elderly patients - Chan, Kai Siang (2023)
Background: Mortality of pyogenic liver abscess (PLA) is high ranging 10%–40%. Old age predicts outcomes in many diseases but there is paucity of data on PLA outcomes. We aim to compare the morbidity and mortality between elderly and non-elderly in PLA. Methods: This is a retrospective study from 2007–2011 comparing elderly (≥ 65 years old) and non-elderly (< 65 years old) with PLA. A 1:1 propensity score matching (PSM) was performed. Baseline clinical profile and outcomes were compared. Results: There were 213 patients (elderly patients = 90 [42.3%], non-elderly patients = 123 [57.7%]). Overall median age is 62 (interquartile range [IQR] = 53–74) years old. PSM resulted in 102 patients (51 per arm). Length of hospitalisation stay (LOS) was significantly longer in elderly patients in both unmatched (16 [IQR = 10–24.5] versus 11 [IQR = 8–19] days; P < 0.001) and matched cohorts (17 [IQR = 13–27] versus 11 [IQR = 7–19] days; P = 0.001). In-hospital mortality was significantly higher in elderly patients in the unmatched cohort (elderly patients = 21.1%, nonelderly patients = 7.3%; P = 0.003) but was insignificant following PSM (elderly patients = 15.7%, non-elderly patients = 9.8%; P = 0.219). Duration of antibiotic therapy and need for percutaneous drainage (PD) were comparable before and after PSM. Conclusion: Age ≥ 65 years old is associated with longer LOS. In-hospital mortality though higher in elderly patients, was not statistically significant.